ANALISIS EFEKTIVITAS PENERIMAAN PAJAK DAERAH DAN RETRIBUSI DAERAH TERHADAP PENDAPATAN ASLI DAERAH KABUPATEN/KOTA DI PROVINSI GORONTALO - Agisthi Shinta Az-zahra; Rino Rinaldo; Elvia Fardiana (Akuntansi research UGR, 2024)
This research aims to measure the level of effectiveness of regional taxes and regional levies and their contribution to district/city original regional income in Gorontalo province during the 2017-2021 period. The data used in this research is secondary data originating from reports on targets and realization of regional taxes, regional levies, and Regional Original Income (PAD) from 2017 to 2021. This data is accessed via the official website of the Directorate General of Fiscal Balance, Ministry of Finance (djpk.kemenkeu.go.id). The data collection technique used in this research is through documentation and literature study methods and the data analysis technique uses quantitative descriptive analysis. The research results show that the level of effectiveness of regional tax revenues is as follows: (1) Kab. Boalemo and Kab. North Gorontalo are very effective, Kab. Gorontalo and Kab. Pohuwanto are effective, Gorontalo City is quite effective and Kab. Bone Bolango is Less effective. (2) The level of regional tax contribution to regional original income (PAD) is that Kab. Boalemo, Kab. Bone Bolango, Kab. Gorontalo and Kab. Pohuwanto are in the Less category. Kab. North Gorontalo and Gorontalo City are in the Medium category (3). The results of the effectiveness level of regional levy revenue is Kab. North Gorontalo is very effective, Kab. Boalemo and Kab. Gorontalo are effective and Kab. Bone Bolango, Kab. Pohuwanto and Gorontalo City are less effective. (4) The level of contribution of regional levies to Original Regional Income (PAD) is known to Kab. North Gorontalo is in the medium category and Kab. Pohuwanto is in the poor category, then Kab. Boalemo, Kab. Bone Bolango, Kab. Gorontalo and Gorontalo City are in the very poor category.